2008
DOI: 10.3122/jabfm.2008.06.080025
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control and Pharmacotherapy Patterns in the United States Before and After the Release of the Joint National Committee on the Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 7) Guidelines

Abstract: Methods: This was a retrospective, time series analysis of 27 provider groups and managed care organizations from 1998 through 2006. Patients with hypertension were identified from more than 4000 physicians. Medical charts were collected and clinical data were evaluated using prevailing JNC criteria during the time period before and after JNC 7.Results: A total of 19,258 patients were identified with hypertension: 15,258 included in the before-JNC 7 cohort and 4,000 in the after-JNC 7 cohort. BP control in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…3,8,9 In the present study, maximum numbers of patients were in the age group of 50-59 years these results were similar to the earlier study and 71.1% of the patients had a family history of hypertension reinforces the fact that there is a strong genetic predisposition in hypertension.…”
Section: Discussionsupporting
confidence: 81%
“…3,8,9 In the present study, maximum numbers of patients were in the age group of 50-59 years these results were similar to the earlier study and 71.1% of the patients had a family history of hypertension reinforces the fact that there is a strong genetic predisposition in hypertension.…”
Section: Discussionsupporting
confidence: 81%
“…3,24,25 In an analysis of a retrospective time series data from 27 provider groups and managed-care organizations between 1998 and 2006, Jackson et al 26 reported that the proportion of all hypertensive patients with disease-specific BP control rates rose from 40.8% before JNC 7 to 49.3% after JNC 7. Another managed-care organization study recently showed that JNC 7 BP control goals were not achieved among most hypertensive patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…In 1977, the Joint National Committee on the Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC) published its first hypertension guideline. In JNC 1 and JNC 2, the diagnosis and management of hypertension was based on diastolic blood pressure (DBP) only, with normal defined as <90 mmHg, and therapy recommended for individuals with a DBP of ≥105 mmHg, while it could be considered in those with a DBP of 90-104 mmHg [6,7]. The goal of therapy was to decrease DBP into the normal range (<90 mmHg).…”
Section: Introductionmentioning
confidence: 99%